Molecular Pathology of Pulmonary Edema in Forensic Autopsy Cases with Special Regard to Fatal Methamphetamine Intoxication. Issue 6 (21st September 2016) - Du, Yu; Jin, Hong‐Nian; Zhao, Rui; Zhao, Dong; Xue, Ye; Zhu, Bao‐Li; Guan, Da‐Wei; Xie, Xiao‐Li; Wang, Qi
Abstract: Pulmonary edema is a common finding in fatal methamphetamine intoxication. However, the underlying mechanism remains poorly understood. This study investigated the molecular pathology of alveolar damage involving pulmonary edema in forensic autopsy cases. Seven candidate reference genes (RPL13A, YWHAZ, GUSB, SDHA, GAPDH, B2M, and ACTB) were evaluated in the lung by the geNorm module in qBase plus software. RPL13A, YWHAZ, and GUSB were identified as the most stable reference genes. Using these validated reference genes, intrapulmonary mRNA expressions of matrix metalloproteinases (MMPs), intercellular adhesion molecule‐1 (ICAM‐1), claudin‐5 (CLDN‐5), and aquaporins (AQPs) were examined. Relative mRNA quantification using TaqMan real‐time PCR assay demonstrated higher expressions of all markers except for AQP‐5 in fatal METH intoxication cases. These findings suggested alveolar damage and compensatory response in fatal METH intoxication cases. Systematic analysis of gene expressions using real‐time qPCR is a useful tool in forensic death investigation.